Overview on the potential of renewable energy generation in poultry farms: A case study in the Manjung Region, Malaysia - Manogaran, M. Devendran; Shamsuddin, Rashid; Yeow, Khai Zhi; Lim, Jun Wei; Hakimi, Mohd; Siyal, Ahmer Ali (Science, Engineering and Health Studies, 2025)
Poultry farming in the Manjung region of Malaysia is constantly expanding to accommodate the country’s increase in protein intake. Consequently, poultry farming is facing problems such as high usage of energy and carbon emissions from waste due to a lack of energy alternatives and poor waste management. The purpose of this study is to evaluate the economic feasibility of introducing biogas and solar energy as an alternative energy source in broiler houses. The effectiveness of green energy to sustain the daily operations in the poultry farm was evaluated by calculating and comparing the energy generation from the aforementioned sources, thus reducing dependence on the national power grid and having more affordable, sufficient and environmentally benign energy. For the biogas production, waste from the poultry farms was anaerobically digested to produce methane and carbon dioxide and later methane was used to produce energy through combustion. On the other hand, solar energy was trapped via the photovoltaic modules and converted into electricity which could be used for lighting and ventilation in the poultry farm. Each cycle of biogas production depicted the potential amount of electricity generation at 27,452.04 kWh, which had a surplus of 15,522.04 kWh per cycle. By installing a 100-kW solar system in 25% of the total roofing area of broiler houses in Manjung, with the capacity of producing 12,000 kWh per month when optimal angle of installation of solar panel is achieved, a 5% grid consumption reduction through photovoltaic would be obtainable. This approach has the potential to advance the circular economy within the poultry industry, while also promoting the adoption of carbon-neutral farming practices.